The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1099/ijs.0.02777-0
|View full text |Cite
|
Sign up to set email alerts
|

Proposal to elevate the genetic variant MAC-A, included in the Mycobacterium avium complex, to species rank as Mycobacterium chimaera sp. nov.

Abstract: The possibility that the strains included within the Mycobacterium avium complex (MAC), but not belonging either to M. avium or to Mycobacterium intracellulare, may be members of undescribed taxa, has already been questioned by several taxonomists. A very homogeneous cluster of 12 strains characterized by identical nucleotide sequences both in the 16S rDNA and in the 16S–23S internal transcribed spacer was investigated. Similar strains, previously reported in the literature, had been assigned either to the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
197
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(212 citation statements)
references
References 36 publications
8
197
0
3
Order By: Relevance
“…Previous North American studies have suggested that M. intracellulare is the more common pulmonary pathogen within the MAC (1). We identifi ed 3 pulmonary samples as MAC-A strains, which were recently elevated to species level as M. chimaera (7). Two samples were clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Previous North American studies have suggested that M. intracellulare is the more common pulmonary pathogen within the MAC (1). We identifi ed 3 pulmonary samples as MAC-A strains, which were recently elevated to species level as M. chimaera (7). Two samples were clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Ante la facilidad del método de PCR-análisis de restricción, en el mundo se han realizado una serie de estudios para lograr su estandarización y probar la reproducibilidad de la técnica (21). La principal ventaja de PCR-análisis de restricción es que, siendo un método de amplificación, desde la muestra se puede identificar la especie, en corto tiempo y con gran efectividad (18); en la mayoría de los casos, es capaz de diferenciar entre especies de los grupos de micobacterias, como el complejo M. aviumintracellulare de gran importancia clínica, aunque no diferencia los nuevos miembros del complejo, que son M. chimaera y M. colombiense (22)(23).…”
unclassified
“…abscessus, M. mucogenicum, M. salmoniphilum, M. bolletii and M. massiliense (Brown-Elliot & Wallace, 2002;Whipps et al, 2007) and the M. fortuitum complex, including M. fortuitum, M. peregrinum, M. septicum, M. mageritense, M. houstonense and M. boenikei (Adékambi & Drancourt, 2004), containing the NTM commonly encountered in human specimens. Clinically important SGM are the M. avium complex (MAC), which include M. avium, M. intracellulare, M. colombiense and M. chimaera (Tortoli, 2003;Tortoli et al, 2004).…”
Section: Introductionmentioning
confidence: 99%